A user-friendly clinical practice guideline summary for managing low back pain in South Africa - Jessica Stander; Karen Grimmer; Yolandi Brink (AOSIS, 2020)
Background: Clinical practice guidelines (CPGs) provide conveniently packaged evidence-based recommendations to inform clinical decisions. However, intended end-users often do not know how to source, appraise, interpret or choose among CPGs. Moreover, it can be confusing when recommendations on the same topic differ among CPGs, in wording, intent and underpinning evidence. Objectives: This article reports on the processes of: (1) identifying current CPGs for acute and subacute low back pain (LBP) to fit the needs of South African physiotherapists, (2) collating and summarising CPG recommendations to produce a user-friendly end-user product and (3) testing the utility of the summary CPG document on South African physiotherapy clinicians to efficiently determine acceptability, appropriateness and feasibility to inform clinical decision-making. Method: An adapted approach was followed by systematically searching online CPG repositories and online databases for LBP CPGs; screening and critically appraising identified CPGs; summarising recommendations from relevant CPGs and organising them into clinical practice activities. Feedback on utility was obtained from 11 physiotherapists. Results: Three high-quality, international CPGs provided 25 recommendations on the assessment and management of acute and subacute LBP relevant to South African physiotherapy practice. They were organised into 10 headings. Physiotherapy user feedback suggested that this document would assist in clinical decision-making. Conclusion: Organised recommendations extracted from multiple, relevant CPGs provide an end-user-friendly resource for physiotherapists treating LBP. Clinical implications: Collated and organised CPG recommendations may effectively assist South African physiotherapists' clinical decision-making in assessing and managing patients with acute and subacute LBP.